MiR-1181 inhibits stem cell-like phenotypes and suppresses SOX2 and STAT3 in human pancreatic cancer. Issue 2 (28th January 2015) - Jiang, Jianxin; Li, Zhu; Yu, Chao; Chen, Meiyuan; Tian, Se; Sun, Chengyi
Highlights:   MiR-1181 is downregulated in pancreatic cancer and associated with short survival and high recurrence.    Overexpressing miR-1181 inhibited, whereas inhibiting miR-1181 promoted, CSCs-like phenotypes in pancreatic cancer cells.    MiR-1181 directly suppressed SOX2 and STAT3 expression, leading to SOX2 deregulation and STAT3 pathway deactivation. Abstract: Recent studies have shown that cancer stem cells (CSCs) play an important role in the development of pancreatic cancer. Multiple oncogenes and signaling pathways have been confirmed to participate in the stemness maintenance and tumorigenicity of CSCs, including sex-determining region Y-box 2 (SOX2) and signal transduction and activation of transcription 3 (STAT3), which may provide novel therapeutic targets on pancreatic cancer. Here, we reported in pancreatic cancer tissues and cells that miR-1181 expression was markedly downregulated, and the low miR-1181 expression was associated with poorer overall survival and disease-free survival in pancreatic cancer patients. Furthermore, overexpression of miR-1181 inhibited, whereas downregulation of miR-1181 promoted, CSCs-like phenotypes in vitro and tumorigenicity in vivo in pancreatic cancer cells. Moreover, we demonstrated that miR-1181 directly suppressed SOX2 and STAT3 expression, resulting in downregulation of SOX2 and inhibition of the STAT3 pathway. Hence, our results suggest that miR-1181 plays a vital role in inhibiting the CSCs-like phenotypes in pancreatic cancer and might represent a potential target for anti-pancreatic cancer.